CASE STUDY OF CLAIM AGAINST VIOLENCE IN HOUSEHOLD IN RELIGION COURT OF CLASS I A BENGKULU - Edytiawarman Edytiawarman; Slamet Muljono; Dimas Dwi Arso (Bengkoelen Justice : Jurnal Ilmu Hukum, 2020)
This study aims to determine what factors cause one of the parties to commit domestic violence and how is the judge's consideration in completing the case for divorce due to domestic violence in the Class I A Bengkulu Religious Court. In this study the authors use a normative juridical approach, also called research on doctrinal law that is the law conceptualized as what is written in the legislation or law conceptualized as a rule or norm which is a benchmark of human behavior that is considered appropriate. In this study, what was sought was the decision of the Bengkulu Class Religion Court in deciding the case for divorce due to domestic violence. In this study the authors used a type of descriptive research, which is to provide as much detailed data as possible about human conditions or other symptoms. This descriptive method is intended to obtain a good, clear picture and can provide as much detailed data as possible about the object under study. In this case to describe the divorce due to domestic violence. The results of this study are expected to be used as a reference in conducting legal counseling in the city of Bengkulu to increase community legal awareness that domestic violence is contrary to applicable laws and regulations and as a reference material for the enrichment of civil law teaching materials in general and marriage law in general. especially.